Comparison Study of the Bio-Plex and Meso Scale Multiplexed SARS-CoV-2 Serology Assays Reveals Evidence of Diminished Host Antibody Responses to SARS-CoV-2 after Monoclonal Antibody Treatment - Urvi Parikh; Amy Heaps; Daniela Moisi; Kelley Gordon; John Mellors; Manish Choudhary; Rinki Deo; Carlee Moser; Paul Klekotka; Alan Landay; Judith Currier; Joseph Eron; et al. (Case Western Reserve University, 2024)
Background: Assessing the breadth and duration of antigen-specific binding antibodies provides valuable information for evaluating interventions to treat or prevent SARS-CoV-2 infection. Multiplex immunoassays are a convenient method for rapid measurement of antibody responses but can sometimes provide discordant results, and antibody positive percent agreement for COVID-19 diagnosis can vary depending on assay type, disease severity, and population sampled. Therefore, we compared two assays marked for research applications, MSD and Bio-Plex Pro, to evaluate qualitative interpretation of serostatus and quantitative detection of antibodies of varying isotypes (IgG, IgM, and IgA) against receptor binding domain (RBD) and nucleocapsid (N) antigens. Methods: Specimens from ACTIV-2/A5401, a placebo-controlled clinical trial of the SARS-CoV-2 monoclonal antibody (mAb) bamlanivimab to prevent COVID-19 disease progression, were used to evaluate the concordance of the Bio-Rad Bio-Plex Pro Human SARS-CoV-2 Serology Assay and the Meso Scale Discovery (MSD) V-PLEX COVID-19 Panel 1 serology assay in detecting and quantifying IgG, IgA, and IgM binding anti-SARS-CoV-2 antibody responses against the RBD and N antigens. Data were disaggregated by study arm, bamlanivimab dose, days post-enrollment, and presence of emerging resistance. Results: We observed 90.5% (412 of 455 tests) concordance for anti-RBD IgG and 87% (396 of 455) concordance for anti-N IgG in classifying samples as negative or positive based on assay-defined cutoffs. Antibody levels converted to the WHO standard BAU/mL were significantly correlated for all isotypes (IgG, IgM, and IgA) and SARS-CoV-2 antigen targets (RBD and N) tested that were common between the two assays (Spearman r 0.65 to 0.92, P < 0.0001). Both assays uncovered evidence of diminished host-derived IgG immune responses in participants treated with bamlanivimab compared to placebo. Assessment of immune responses in the four individuals treated with the 700 mg of bamlanivimab with emerging mAb resistance demonstrated a stronger anti-N IgG response (MSD) at day 28 (median 2.18 log BAU/mL) compared to participants treated with bamlanivimab who did not develop resistance (median 1.55 log BAU/mL). Conclusions: These data demonstrate the utility in using multiplex immunoassays for characterizing the immune responses with and without treatment in a study population and provide evidence that monoclonal antibody treatment in acute COVID-19 may have a modest negative impact on development of host IgG responses.